Studi Kasus Deskriptif Transisi Kepemimpinan Gembala Sidang di Gereja Jemaat Kristen Indonesia Wilayah Semarang - Ratna Setiowati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In this era of globalization, women as leaders are not only in the secular world. Women's leadership in the spiritual world has emerged, one of which is when a woman is appointed as a pastor. To become a good leader, you can prepare yourself by learning about leadership. However, there are also those who have not had the chance to learn about leadership but have been appointed as leaders. This happens when a pastor's wife is suddenly appointed as a church leader in urgent conditions due to the death of her husband. This case was experienced by several pastors of the JKI Synod of the Semarang Regional Coordination as pastors replacing their husbands who died. In this study, the author aims to find out when a leadership transition occurs, is the pastor's wife ready to lead? How does the congregation respond to the transition of leadership from husband to pastor's wife? When the transition occurs, is there progress or decline in terms of the number of congregations, church management systems. In this study, the author uses a qualitative method with a case study approach. Where the author collects data by interviewing participants as a source of information. In addition to interviews, literature related to leadership is also used. Thus, it is expected that the results of this study can provide a solution when there is a transition of leadership in the church, the wife is ready to shepherd by having leadership skills so that it will not cause problems when someone accepts the transition of leadership and can be applied in Christian leadership